Student's Preferences in Using Video-Based Learning Applications and Its Efficiency in Higher Education - Sufirmansyah Sufirmansyah; Laudria Nanda Prameswati; Dewi Trisna Wati; Endang Sulistyowati (Nazhruna: Jurnal Pendidikan Islam, 2021)
The aim of this article is to discover students' preferences for using video-based learning applications as well as their efficiency in supporting distance learning in higher education. This article was based on research conducted using descriptive qualitative methods. Data were collected from 100 PAI students at IAIN Kediri using a closed interview technique via Google Form. The authors also conducted a review of various kinds of literature from a number of relevant previous studies to strengthen this research. According to the findings of this research, PAI students are used to using two video-based learning applications during distance learning, namely Google Meet and Zoom Meeting. 64 percent of students, on the other hand, prefer the Google Meet app. Google Meet is considered more efficient because it requires less RAM capacity, uses fewer data packages, and can be accessed via a browser without the need to first download an application.